Achaios : studies presented to Professor Thanasis I. Papadopoulos - Papadopoulou-Chrysikopoulou, Evangelia; Papadopoulou-Chrysikopoulou, Evangelia; Chrysikopoulos, Vassilis; Chrysikopoulos, Vassilis; Christakopulu-Sōmaku, Giulika; Christakopulu-Sōmaku, Giulika (Archaeopress, 2016)
In 'Achaios', 35 scholars from six different countries have contributed with 31 papers, as a small token of appreciation, gratitude and affection to a true scholar, who devoted his life studying and revealing the long journeys of the Mycenaeans and their culture